Identification of Local Wisdom of Ogan Ilir Regency in South Sumatra as Resource for Learning Physics in High School - Lia, Linda; Susilawati, Sulistiawati; Sugiarti, Sugiarti (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2024)
This research aims to discover whatever local wisdom in Ogan Ilir Regency, South Sumatra, can be used as a resource for learning physics in high school as well as whatever basic competencies in physics subjects can be integrated with the local wisdom of Ogan Ilir Regency, South Sumatra. This research was qualitative in nature. The data analysis techniques used was the Miles and Huberman model consisting of data collection, data reduction, data display, and conclusion drawing. Based on the findings there are six local wisdoms in Ogan Ilir Regency that can serve as resource for learning Physics in high school, namely: the Knock-Down House from Tanjung Batu, Dodol from Tebing Gerinting, Mapak Raje Dance from Indralaya, Gebeng cloth from Limbang Jaya Tanjung Batu, Mande skill from Tanjung Dayang, and Syarofal 'Anam (Terbangan) from Indralaya. There are six basic competencies in the physics subject in high school that can be integrated with the local wisdom of Ogan Ilir Regency, two (3.1 and 3.7) from class X and four (3.2, 3.3., 3.5, 3.8.) from class XI.